Obstetric professionals' perceptions of non-invasive prenatal testing for Down syndrome: clinical usefulness compared with existing tests and ethical implications - Olivia Miu Yung Ngan; Huso Yi; Samuel Yeung Shan Wong; Daljit Sahota; Shenaz Ahmed (BMC, 2017)
Abstract Background While non-invasive prenatal testing (NIPT) for fetal aneuploidy is commercially available in many countries, little is known about how obstetric professionals in non-Western populations perceive the clinical usefulness of NIPT in comparison with existing first-trimester combined screening (FTS) for Down syndrome (DS) or invasive prenatal diagnosis (IPD), or perceptions of their ethical concerns arising from the use of NIPT. Methods A cross-sectional survey among 327 obstetric professionals (237 midwives, 90 obstetricians) in Hong Kong. Results Compared to FTS, NIPT was believed to: provide more psychological benefits and enable earlier consideration of termination of pregnancy. Compared to IPD, NIPT was believed to: provide less psychological stress for high-risk women and more psychological assurance for low-risk women, and offer an advantage to detect chromosomal abnormalities earlier. Significant differences in perceived clinical usefulness were found by profession and healthcare sector: (1) obstetricians reported more certain views towards the usefulness of NIPT than midwives and (2) professionals in the public sector perceived less usefulness of NIPT than the private sector. Beliefs about earlier detection of DS using NIPT were associated with ethical concerns about increasing abortion. Participants believing that NIPT provided psychological assurance among low-risk women were less likely to be concerned about ethical issues relating to informed decision-making and pre-test consultation for NIPT. Conclusions Our findings suggest the need for political debate initially on how to ensure pregnant women accessing public services are informed about commercially available more advanced technology, but also on the potential implementation of NIPT within public services to improve access and equity to DS screening services.